An ANALYSIS OF CHANGES IN SPEAKING MANNERS BY MIXING INDONESIAN AND ENGLISH: A CASE STUDY OF GENERATION Z TEENAGERS - Rizky Sormin; Ika Purnama Sari; Anita Purba (Epigram, 2025)
This study explores the linguistic phenomenon of code-mixing between Indonesian and English among Generation Z teenagers. It aims to analyze how the integration of English into daily conversations influences their speaking manners, including lexical choices, sentence structures, and sociolinguistic implications. A qualitative case study approach was employed, involving interviews, discourse analysis, and surveys among teenagers in urban areas. The findings indicate that code-mixing is used for stylistic expression, social identity formation, and digital communication adaptation. While it enhances bilingual proficiency, it also raises concerns about language shift and cultural identity. The study provides insights into the evolving linguistic patterns of Generation Z and their implications for language education and communication norms.